Analisa Operasi Ekonomis Pembangkit Termal untuk Melayani Beban Puncak Sistem Kelistrikan Sumbar - Syafii, Syafii; Ika Putri, Kartika (JURNAL NASIONAL TEKNIK ELEKTRO, 2018)
The economical operation of electric power systems is an important aspect in energy system management. The research aim is analyzing the economical operation of thermal generators by performing calculations to obtain optimal power and minimum generation costs, using the lamda iteration method. The case study of the operation of the plant in serving the peak load is taken on the West Sumatera electrical system with the assumption that the thermal generator units used are the PLTD, PLTG Pauh Limo, and PLTU Ombilin power plant. The power demand (PD) to be serviced by the thermal generator is 76.8 MW taken from 15% of maximum load duration curve 512 MW. The distribution of load demand for each thermal generating unit obtained through the economic dispatch calculation. The resulted of economical operation of the thermal generator P1 = 1,25 MW, P2 = 15,867 MW, and P3 = 59,683 MW with total generation cost 57,295,977.57 IDR/h. The calculation and comparison with other configuration scheduling results showed that by using economic dispatch method in power generation scheduling, has obtained efficient generation configuration with minimum operating cost to serve the peak load. Thus, the generation cost can be saved as the generation capacity can be optimized or operated in accordance with the calculation of economic operation.Keywords : Thermal Power Plant, Economic Dispatch, Lamda Iteration MethodAbstrakOperasi ekonomis sistem tenaga listrik merupakan aspek penting dalam manajemen sistem energi. Penelitian ini bertujuan melakukan analisa operasi ekonomis pembangkit termal dengan melakukan perhitungan untuk mendapatkan daya yang optimal serta biaya pembangkitan minimum, dengan  menggunakan metode iterasi lamda. Studi kasus operasi pembangkit dalam melayani beban puncak diambil pada sistem kelistrikan Sumbar dengan asumsi unit pembangkit termal yang digunakan adalah PLTD, PLTG Pauh Limo, dan PLTU Ombilin. Besar daya beban (PD) yang akan dilayani oleh pembangkit termal tersebut diambil 15 % dari kurva lama beban harian maksimum 512 MW yaitu 76,8 MW. Pembagian pembebanan untuk masing-masing unit pembangkit termal diperoleh melalui perhitungan economic dispatch. Hasil perhitungan operasi ekonomis untuk masing-masing pembangkit termal tersebut adalah P1 = 1,25 MW, P2 = 15,867 MW, dan P3 = 59,683 MW dengan total biaya pembangkitan Rp 57.295.977,57 per jam. Hasil perhitungan dan perbandingan dengan konfigurasi penjadwalan lainnya memperlihatkan bahwa dengan menggunakan perhitungan operasi ekonomis dalam penjadwalan pembangkit, telah diperoleh konfigurasi pembangkitan yang efisien dengan biaya operasi minimum untuk melayani beban puncak.  Dengan demikian biaya pembangkitan dapat dihemat sekirannya kapasitas pembangkitan dapat dioptimalkan atau dioperasikan sesuai dengan hasil perhitungan operasi ekonomis.Kata Kunci :  Pembangkit Termal, Economic Dispatch, Metode Iterasi Lamda